A glossary of English grammar - Leech, Geoffrey N. (Edinburgh University Press, 2006)
A Glossary of English Grammar presents a wide range of terms used to describe the way the English language is structured. Grammatical terms can be a problem for students, especially when there are alternative names for the same thing (for example, 'past tense' and 'preterite'). This book therefore provides a basic and accessible guide, focusing on the English language. Definitions of grammatical terms are given in simple language, with clear examples, many from authentic texts and spoken sources, showing how they are used. The terms used in the Comprehensive Grammar of the English Language are widely seen as standard, and form the basis of grammatical terminology in this book. At the same time, this glossary does not neglect other variants of English grammar, such as that of Huddleston and Pullum's influential Cambridge Grammar of the English Language, whose most important terms are also covered here. This book is indispensable for anyone wishing to understand present-day terminology of English grammar more fully. Key Features: A handy and easily understandable pocket guide for anyone studying the structure of the English language Supplies numerous cross-references to related terms Includes an annotated bibliography with suggestions for further reading.
Keywords: English language -- Grammar -- Glossaries, vocabularies, etc.; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- General.; LANGUAGE ARTS & DISCIPLINES -- Grammar & Punctuation.; LANGUAGE ARTS & DISCIPLINES -- General.; English language -- Grammar; 18.04 English language.; Englisch; Grammatik; Grammar.; English.; Englische Sprache -- Grammatik -- Wörterbuch; English language -- Grammar -- Dictionaries; Englisch.; Glossaries, vocabularies, etc.; Wörterbuch; Dictionaries (form); Reference works.; Ouvrages de référence.